JUSTIFICATION AND SELECTION OF OPTIMAL OPERATION OF GAS LIFT WELLS - Mukhammadiyev, Khamidullo (Innovatsion texnologiyalar, 2023)
This article develops recommendations on the use of the gas lift method for the artificial creation of fountains in the wells of under-gas oil fields. To determine the optimal operating mode of a gas-lift well, a calculation was made of the movement of the gas-liquid mixture through the well. In order to avoid reducing the efficiency of gas use, it is shown that it is necessary to take into account the relative gas flow rate that will be consumed by the gas lift method during well operation.